Atomic-scale investigation of spinel LiFe5O8 thin films on SrTiO3 (001) substrates. (1st March 2020) - Liu, Kun; Zhang, Ruyi; Lu, Lu; Mi, Shaobo; Liu, Ming; Wang, Hong; Wu, Shengqiang; Jia, Chunlin
Abstract: Microstructural properties of spinel LiFe5 O8 (LFO) films grown on (001)-oriented SrTiO3 (STO) substrates have been investigated at the atomic-scale by advanced electron microscopy techniques. Two types of orientation relationship (OR) between the LFO films and the STO substrates have been determined, cube-on-cube and (111)[ 1 ¯ 10]LFO //(111)[1 1 ¯ 0]STO . Antiphase boundaries (APBs) and three types of twin boundaries (TBs) form within the LFO films, and the propagation of TBs and APBs results in their complex interactions. In most cases, interactions between TBs and APBs change the type of TBs and terminate the propagation of APBs since the APBs introduce a displacement vector of ( a /4)〈110〉 into the TBs. In addition, the interactions between two coherent TBs are observed to generate the incoherent TB. The epitaxial strain of the LFO/STO (001) heterosystem can be released by the formation of TBs and APBs in the films and misfit dislocations at the interface. Considering that the magnetic coupling across the APBs and TBs can lead to novel physical properties, the appearance of APBs and TBs with a high density in the LFO films would affect the magnetic properties of the films.